Photosystem II‐Inhibitors Play a Limited Role in Sweet Corn Response to 4‐Hydroxyphenyl Pyruvate Dioxygenase‐Inhibiting Herbicides. (1st July 2014) - Choe, Eunsoo; Williams, Martin M.; Boydston, Rick A.; Huber, Joan L.; Huber, Steven C.; Pataky, Jerald K.
Abstract : Postemergence (POST) application of 4‐hydroxyphenyl pyruvate dioxygenase (HPPD) inhibitors in combination with a photosystem II (PSII) inhibitor, such as atrazine [6‐chloro‐N‐ethyl‐N9‐(1‐methylethyl)‐1, 3, 5‐triazine‐2, 4‐diamine], is common practice in sweet corn ( Zea mays L.) production. Given the sensitivity of sweet corn to HPPD‐inhibiting herbicides, the objective of this work was to determine the extent to which cytochrome P450 (CYP) genotype and PSII‐inhibitors affect crop sensitivity to HPPD‐inhibiting herbicides. Greenhouse experiments were used to identify PSII‐inhibitors that were least injurious when combined with the HPPD‐inhibitors, mesotrione [2‐(4‐mesyl‐2‐nitrobenzoyl)‐3‐hydroxycylohex‐2‐enone], tembotrione 2‐[2‐chloro‐4‐(methylsulfonyl)‐3‐[(2, 2, 2‐trifluoroethoxy)methyl]benzoyl]‐1, 3‐cyclohexanedione, and topramezone [3‐(4, 5‐dihydro‐3‐isoxazolyl)‐2‐methyl‐4‐(methylsulfonyl)phenyl](5‐hydroxy‐1‐methyl‐1H‐pyrazol‐4‐yl)methanone. Subsequently, HPPD‐inhibitors were tested individually with PSII‐inhibitors atrazine, or bentazon [3‐(1‐methylethyl)‐(1H)‐2, 1, 3‐benzothiadiazin‐4(3H)‐one2, 2‐dioxide], or alone in field experiments on all three CYP genotypic classes; hybrids homozygous for mutant CYP alleles (cypcyp), hybrids homozygous for functional alleles (CYPCYP), and heterozygous hybrids (CYPcyp). Leaf bleaching within 1 wk of herbicide application increased when a PSII‐inhibitor was combined with an HPPD‐inhibitor; however, the relatively low level of injury was short‐lived. Tank mixing atrazine to mesotrione, tembotrione, or topramezone in sweet corn did not increase risk of yield loss compared to HPPD‐inhibitor applied alone. The synergistic effect on weed control between certain PSII‐ and HPPD‐inhibitor combinations reported previously does not hold true regarding sweet corn sensitivity to these herbicides. Among three HPPD‐inhibitors tested in sweet corn, topramezone was the safest, regardless of PSII combination. Mutant CYP alleles, namely CYPcyp and cypcyp hybrids, are the main cause of sweet corn sensitivity to mesotrione, tembotrione, and other CYP‐metabolized herbicides; therefore, breeding efforts to eliminate mutant CYP alleles should remain a high priority.